FACTORS CONTRIBUTING TO THE SUBOPTIMAL USE OF INSTAGRAM AT HOSPITAL X MALANG - Almira, Anissa Putri; Suryanto; Rozany, Farida (Journal of Community Health and Preventive Medicine, 2025)
Digital marketing leverages digital channels to reach consumers in a targeted, cost-effective, and personalized manner. Social media platforms, particularly Instagram, offer hospitals opportunities to interact directly with patients, disseminate information, and build stronger relationships. This study aims to identify the underlying factors contributing to the ineffective use of Instagram as a digital marketing tool at Hospital X and to support efforts to optimize its marketing strategy. A qualitative approach was employed, with data collected through interviews and focus group discussions (FGDs). Interviews were conducted with patients, the Head of Public Relations, and the Hospital Health Promotion Unit (PKRS), while FGDs involved the hospital director, division heads, and department heads. Data were thematically analyzed and subjected to root cause analysis to identify key issues. Three primary factors were identified as barriers to effective digital marketing implementation: (1) lack of specialized digital marketing training, (2) insufficient human resources preventing the formation of a dedicated team, and (3) limited awareness across departments to contribute regular content. These challenges collectively hinder the hospital’s ability to optimize its use of Instagram. These findings highlight the need for the hospital to strengthen its digital marketing strategy by addressing the three key root causes identified in this study.